Community Empowerment Through Entrepreneurship Program Based on Information Technology (Technopreneurship) for Residents of RT 03 RW 02 Pondok Jati Jurangmangu Barat Pondok Aren - Agus Umar Hamdani; Indra; Wahyuni (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2021)
Residents in the neighborhood of Rukun Tetangga 03 Rukun Warga 02 Pondok Jati Jurangmangu Barat Pondok Aren mostly belong to the lower middle class. Most of the residents in this RT 03 environment run their business businesses such as warungs, drinking water supply services, cellphone counters, workshops, printing houses, internet cafes, house rentals/rents, vehicle rentals, vehicle care services, midwives, and furniture. Although some business actors have used information technology tools to support their business, their use is limited to Facebook, Twitter, Instagram, and WhatsApp. Residents do not understand how to sell and market products using information technology tools. E-Commerce technology is a technology used to conduct business transactions that occur on electronic networks. E-Commerce technology can help market products, especially when implementing large-scale social restrictions (PSBB). Based on the above conditions, we conducted training to build a business using Electronic Commerce (E-Commerce) technology for residents to foster an entrepreneurial spirit based on information technology. the methodology in this community service activity uses the Participatory Rural Appraisal (PRA) approach which consists of the identification of problems, planning activities, implementing activities, monitoring activities, and evaluating community service activities. The output of this community service activity is that the residents of Rukun Tetangga 03 Rukun Warga 02 Pondok Jati Jurangmangu Barat Pondok Aren gain knowledge and experience on how to use E-Commerce technology to support their business activities. For this community service activity to run optimally, it is necessary to provide assistance during the adaptation process of E-Commerce technology and conduct training on digital marketing in the future.